Sensor Controlled Defense Purpose Robot for Land Mine Detection. - Kunaraj, A.; Joy Mathavan, J.; Mathushan, M.; Kamalesan, G.M. (Proceedings of the International Conference on Smart Electronics and Communication (ICOSEC 2020) IEEE Xplore, 2020)
This paper presents an automated metal detecting rover-robot which can be operated by remote to help in the landmine detection. The objective of this metal detector robot is to identify the landmines in war-affected rehabilitation places. The detection of landmines through this proposed method is free of risk and less human effort. Integration of inductive sensor, video camera and ATUNO microcontroller are used here to discover landmines. The system functions using radio frequency (RF) module for device control and Bluetooth module for communication between operator and robot. While experimenting, this robot shows high metal detection ability which is competent enough to be used in the applications in landmine covered regions.
Keywords: Metal detector; Robot; Landmine; Defense purpose; Arduino UNO microcontroller Issue date: 2020